Representation of a solution of the Cauchy problem for an oscillating system with two delays and permutable matrices - Diblik, J.; Fečkan, M.; Pospíšil, M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We represent a solution of a nonhomogeneous second-order differential equation with two delays using matrix functions under the assumption that the linear parts are given by permutable matrices.